KARAKTERISASI TEPUNG KONJAK DARI TANAMAN ILES-ILES (AMORPHOPHALLUS ONCOPHYLLUS) DI DAERAH GUNUNG KREO SEMARANG JAWA TENGAH - Hafiz Akbar; Agus Supriyanto; Kristinah Haryani (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Indonesia has many kinds of plants iles-iles (Amorphophallus oncophyllus). In this study, using raw materials derived from the Goa Kreo, Semarang, Central Java, the area has two types of iles-iles, namely A. oncophyllus and A. variabillis. Plants iles-iles (konjac) contains a fairly high Glukomannan, glukomannan is a polysaccharide composed of units of D-glucose and D-mannose. In this study intended to determine the content of glucomannan plant iles-iles in Goa Kreo. By using gravimetric methods phenyl hydrazine, glucomannan levels were obtained at 30.56%. In this study also aims to determine the viscosity of konjac flour are affected by operating conditions such as the total concentration of konjac flour, stirring time, and pH (pH 2-8). With a higher sucrose concentration, viscosity konjac flour tends to decrease. For salt concentrations (0, 10; 20% w / v) no effect on the viscosity. Improved high viscosity can be observed mixture for konjac - rice flour, konjac - wheat flour and konjac - corn flour. For gel formation, the hydrocolloid which interacts synergistically with konjac flour to form a gel. Hydrocolloids are carrageenan. This gel texture varies according to the ratio of konjac flour - carrageenan.